Lysine-specific demethylase 5C promotes hepatocellular carcinoma cell invasion through inhibition BMP7 expression. Issue 1 (December 2015) - Ji, Xuening; Jin, Shi; Qu, Xiaotong; Li, Kejun; Wang, Hongjiang; He, Hui; Guo, Fuchao; Dong, Lei
Abstract Background Hepatocellular carcinoma (HCC) is the most common type of tumor and is associated with high morbidity and mortality rates. Patients with HCC routinely undergo surgery followed by adjuvant radiation therapy and chemotherapy. Despite such aggressive treatment approaches, median survival times remain under 1 year in most cases. KDM5C is a member of the family of JmjC domain-containing proteins that removes methyl residues from methylated lysine 4 on histone H3 lysine 4 (H3K4). KDM5C has been proposed as an oncogene in many types of tumors; however, its role and underlying mechanisms in HCC remain unclear. Methods Expression level of KDM5C was examined by RT-PCR, and IHC. Forced expression of KDM5C was mediated by retroviruses, and KDM5C was downregulated by shRNAs expressing lentiviruses. Migration and invasion of HCC cells was measured by wound healing, Transwell and Matrigel assays respectively. Results In this study, we report that KDM5C is abundantly expressed in invasive human HCC cells. Cellular depletion of KDM5C by shRNA inhibited HCC cell migration, invasion and epithelial-mesenchymal transitionin vitro, and markedly decreased the metastasis capacity of invasive HCC cells in the liver and lung. Furthermore, ectopic expression of KDM5C in HCC cells promoted cell migration, invasion and epithelial-mesenchymal transition via the inactivation of BMP7. Knockdown of BMP7 significantly promotes shKDM5C-induced cell migration inhibition. Conclusions Taken together, these data suggest that KDM5C-mediated BMP7 inactivation is essential for HCC cell invasion.